Attitude Control of Quadrotor Using PD Plus Feedforward controller on SO(3) - Almido H Ginting; Oyas Wahyunggoro; Adha Imam Cahyadi (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper proposes a simple scheme of Proportional-Derivative (PD) plus Feedforward controller on SO(3) to control the attitude of a quadrotor. This controller only needs the measurement of angular velocity to calculate the exponential coordinates of the rotation matrix. With rotation matrix as an error variable of the controller, the simulation shows that the controller is able to drive the attitude of the quadrotor from hovering condition to desired attitude and from an attitude condition goes to the hovering condition, despite the system is disturbed. When the system is convergent, the rotation error matrix will be a 3x3 identity matrix.